THE PROBLEMATIC ISSUES OF FINANCIAL SUPPORT OF MILITARY UNITS IN THE CONTEXT OF THE TRANSITION TO NATO STANDARDS - Близнюк, Н.; Погрецька, О. (Київський національний університет імені Тараса Шевченка, 2021)
The article analyzes the features of financial support for the defense of military formations as the main subjects in national security and defense in the context of the transition to NATO standards. Their effective organization and functioning is one of the fundamental factors of an effective mechanism of public administration, and depends on a number of different factors. The main reasons for the transition to NATO standards and their categories are described. The funds circulating in military units, institutions, organizations of the Ministry of Defense of Ukraine are classified. Expenditures and crediting of the state budget of Ukraine for the maintenance of the Armed Forces of Ukraine are analyzed. A comparative analysis of the structure of expenditures from the budget of the Ministry of Defense in Ukraine and NATO countries is done. According to international standards, defense spending should be at least 2 % of the planned Gross Domestic Product. If the level of funding is lower than this indicator, it indicates a low level of military and economic security of the country. In Ukraine, which is at the center of an armed conflict, this figure is set at 3 % of Gross Domestic Product. It should be noted that according to NATO norms, defense budget expenditures are distributed as follows: 50 % – for the maintenance of the Armed Forces of Ukraine, 20 % – for the training of troops, 30 % – for the development of armaments and military equipment. In Ukraine, the cost of maintaining the Armed Forces of Ukraine in recent years has ranged from 68-80 % of the total defense budget. The main obstacles to the implementation of financial support and planning procedures in military units are identified. Measures to improve the mechanism of financial support of the Armed Forces of Ukraine are proposed. The transition to NATO standards needs to be considered much more broadly, as its ultimate goal is to provide all Allies with the necessary forces and means in the event of war. Thus, the decision to bring defense spending into line with NATO requirements is not only a manifestation of a serious attitude to the Alliance's instructions, but also a recognition of the fact that in today's world there are still numerous threats and encroachments on the sovereignty of the Ukrainian Armed Forces.

Проаналізовано особливості фінансового забезпечення оборони військових формувань як основних суб'єктів забезпечення національної безпеки та оборони країни в контексті переходу на стандарти НАТО. Ефективна їх організація і функціонування є одним з основоположних чинників дієвого механізму державного управління і залежить від ряду різноманітних за своїм характером чинників. Охарактеризовано основні причини переходу на стандарти НАТО та їхні категорії. Класифіковано кошти, які обертаються у військових частинах, установах, організаціях Міністерства оборони України. Проаналізовано видатки та кредитування Державного бюджету України на утримання ЗСУ. Здійснено порівняльний аналіз структури витрат із бюджету міністерства оборони в Україні та країнах НАТО. Згідно з міжнародними стандартами видатки на оборону мають становити не менше 2 % від запланованого обсягу ВВП. Якщо ж рівень фінансування нижчий, ніж зазначений показник, це свідчить про низький рівень військово-економічної безпеки країни. Зауважимо, що за нормами НАТО видатки оборонного бюджету розподіляють таким чином: 50 % – на утримання ЗСУ, 20 % – на підготовку військ, 30 % – на розвиток озброєння та військової техніки. В Україні витрати на утримання ЗСУ протягом останніх років коливалися в межах 68–80 % усього оборонного бюджету. Зазначено основні перешкоди щодо здійснення процедур із фінансового забезпечення та планування у військових частинах. Запропоновано заходи для вдосконалення механізму фінансового забезпечення ЗСУ. Питання переходу на стандарти НАТО мають бути розглянуті набагато ширше, адже його кінцевою метою є забезпечення всіх разом членів Альянсу необхідними силами і засобами на випадок війни. Таким чином, рішення щодо приведення витрат на оборону до вимог НАТО є не тільки проявом серйозного ставлення до інструкцій Альянсу, а й визнанням того факту, що в сучасному світі все ще є численні загрози і посягання на суверенітет, захист якого покладено на ЗСУ.   Ключові слова: фінансове забезпечення, ЗСУ, Державний
ПРОБЛЕМНІ ПИТАННЯ ФІНАНСОВОГО ЗАБЕЗПЕЧЕННЯ ВІЙСЬКОВИХ ЧАСТИН У КОНТЕКСТІ ПЕРЕХОДУ НА СТАНДАРТИ НАТО
Keywords: financial support; Armed Forces of Ukraine; National budget; NATO countries; defense spending; фінансове забезпечення; ЗСУ; Державний бюджет; країни НАТО; видатки на оборону